Identification of Candida Sp. Fungi in the Oral Cavity of Active Smokers using the Swab Method - Putra, Yoga Pratama; Qurrohman, Muhammad Taufiq (GLOBAL HEALTH SCIENCE GROUP, 2024)
Active smoker is anyone who directly smokes cigarettes from a burning cigarette. The oral mucosa is the part that can be damaged by smoking. Candida infections usually develop on mucous membranes such as the mouth and are responsible for the appearance of disorders such as candidiasis in the oral cavity.Which has the potential to become fungal. Candida is a species that is often found in the oral cavity. This research aims to determine the presence of Candida.sp fungus in the oral cavity in Petoran village RT 02/RW09 Jebres Surakarta. This research was carried out in November 2023 - June 2024 using descriptive observational research with kuota sampling and 20 samples were taken of the Population of active smokers in Petoran village RT 02/09 Jeberas Surakarta. Samples were taken using the oral mucosa swab method, then cultured on PDA media and observed macroscopically and microscopically with an objective lens magnification of 40x. The data in this study were analyzed using a distribution approach to examine the spread of Candida sp. fungal infections among active smokers in Kampung Petoran. Out of the 20 samples collected, the identification results showed that 14 samples, or 70%, were infected with Candida sp., while the remaining 6 samples, or 30%, tested negative. This distribution of infections indicates that the majority of active smokers in the village were exposed to Candida sp. This analysis provides an initial overview of the prevalence of Candida sp. fungus among active smokers in the area.